2017
DOI: 10.1097/nna.0000000000000433
|View full text |Cite
|
Sign up to set email alerts
|

Accountable Care Organization Implementation Experiences and Rural Participation

Abstract: Background Little is known about how accountable care organizations (ACOs) participate with rural health providers. This pilot study examines ACO participation with rural health clinics (RHCs). Methods Telephone interviews with 8 ACO administrators were conducted to determine the early implementation experiences of these organizations and their participation with rural health providers, such as RHCs, using qualitative content analysis, ACO characteristics and emerging themes from the ACO executive responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 2 publications
0
9
0
1
Order By: Relevance
“…One study identified no relationship between EHR functionality and care management activities [40], but another found that using Certified EHRs and participating in either an ACO or patient-centered medical home (PCMH) was associated with the highest odds of performing population management, care coordination, quality measurement, and communication compared to physicians using a Certified EHR but not participating in an ACO or PCMH [8]. Six qualitative ACO-level studies found that ACO leaders emphasized the importance of health IT capabilities in achieving their quality, population health, or financial goals [162125354142]. Additionally, one study found that ACOs performing highly on quality and financial metrics reported extensive and sophisticated use of EHRs in their organizations as a factor for success [43].…”
Section: Resultsmentioning
confidence: 99%
“…One study identified no relationship between EHR functionality and care management activities [40], but another found that using Certified EHRs and participating in either an ACO or patient-centered medical home (PCMH) was associated with the highest odds of performing population management, care coordination, quality measurement, and communication compared to physicians using a Certified EHR but not participating in an ACO or PCMH [8]. Six qualitative ACO-level studies found that ACO leaders emphasized the importance of health IT capabilities in achieving their quality, population health, or financial goals [162125354142]. Additionally, one study found that ACOs performing highly on quality and financial metrics reported extensive and sophisticated use of EHRs in their organizations as a factor for success [43].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, because the Centers for Disease Control and Prevention (CDC) does not fund COPD programs, state and local public health departments have no local CDC‐generated data to use. An alternative source for gathering COPD data in rural communities is through accountable care organizations (ACOs) . Because COPD‐related health care costs due to disease flare‐ups are very high (e.g., they require more ED visits, hospital admissions, and readmissions), ACOs are demonstrating that it is cost effective to monitor and manage COPD to prevent or minimize acute episodes.…”
Section: Goal 3: Collect Analyze Report and Disseminate Copd‐relatmentioning
confidence: 99%
“…An alternative source for gathering COPD data in rural communities is through accountable care organizations (ACOs). 20,21 Because COPD-related health care costs due to disease flare-ups are very high (e.g., they require more ED visits, hospital admissions, and readmissions), ACOs are demonstrating that it is cost effective to monitor and manage COPD to prevent or minimize acute episodes. The ACO data that are used to monitor COPD care and patients' outcomes could be aggregated to support collaborative efforts in rural communities.…”
Section: Goal 3: Collect Analyze Report and Disseminate Copd-relatmentioning
confidence: 99%
“…However, even as ACOs target their expansion efforts toward rural areas, 14 there is a limited understanding of how rural hospitals are affected by ACOs’ efforts to lower costs and reduce use of acute care services. Given the current precariousness of rural hospital financing, it is important to understand how ACOs affect rural hospitals.…”
mentioning
confidence: 99%